2018
DOI: 10.18632/oncotarget.26038
|View full text |Cite
|
Sign up to set email alerts
|

Panobinostat mediated cell death: a novel therapeutic approach for osteosarcoma

Abstract: Osteosarcoma is an aggressive cancer with a poor long term prognosis. Neo-adjuvant poly-chemotherapy followed by surgical resection remains the standard treatment, which is restricted by multi-drug resistance. If first-line therapy fails, disease control and patient survival rate drop dramatically. We aimed to identify alternative apoptotic mechanisms induced by the histone deacetylase inhibitor panobinostat in osteosarcoma cells.Saos-2, MG63 and U2-OS osteosarcoma cell lines, the immortalized human osteoblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
(58 reference statements)
2
14
0
Order By: Relevance
“…We consistently observed that the HDAC inhibitor panobinostat compromised the survival of all osteosarcoma cell lines at low concentrations. These observations are consistent with studies examining the in vitro effects of panobinostat and other broad‐spectrum HDAC inhibitors such as vorinostat on osteosarcoma cell lines 12,21 . Independent studies conducting an in vitro screen of drug efficacy on three osteosarcoma PDXs also identified HDAC inhibitors and specifically panobinostat as effective at inducing osteosarcoma cell death 20 .…”
Section: Discussionsupporting
confidence: 78%
“…We consistently observed that the HDAC inhibitor panobinostat compromised the survival of all osteosarcoma cell lines at low concentrations. These observations are consistent with studies examining the in vitro effects of panobinostat and other broad‐spectrum HDAC inhibitors such as vorinostat on osteosarcoma cell lines 12,21 . Independent studies conducting an in vitro screen of drug efficacy on three osteosarcoma PDXs also identified HDAC inhibitors and specifically panobinostat as effective at inducing osteosarcoma cell death 20 .…”
Section: Discussionsupporting
confidence: 78%
“…For these drugs we also found in vitro data for effect in osteosarcoma cell lines, separate and independent of the experiments already included in PharmacoDB. These drugs include dinaciclib 31 , panobinostat 32 , trametinib 33 , TAE684 34 (ceritinib), pictilisib 35 , and tozasertib 36 . Interestingly, TAE684 (ceritinib) was previously found to reverse cisplatin resistance in vitro in osteosarcoma by our own sarcoma research group 34 .…”
Section: Gene Sets Regulated By the Mirna Profiles Are Strongly Prognmentioning
confidence: 99%
“…Autophagy is a metabolic and circulatory process in which cells decompose damaged organelles and proteins and release decomposition products [7]. It has been reported that autophagy regulates many pathological and physiological processes, such as cell differentiation and death, immune stress, inflammatory reaction, and antiaging [7][8][9][10][11]. Nevertheless, autophagy had dual effects in the process of tumorigenesis and tumor progression.…”
Section: Introductionmentioning
confidence: 99%